Iowa RBA, October 9-10, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for October 9-10, 1995. Highlights of the update include sightings of a Fish Crow, California Gull, Sabine's Gull, Snowy Egret, Black-legged Kittiwake and five American Avocets. Also included are handwritten notes for the next week's update with sightings of a Black-bellied Plover and a Peregrine Falcon. Epson - sheet feed/flatbed